Carcinoma of The Gingiva Simulating Epulis - A Case Report - Vishnudas Bhandari; Vipin Mahurkar; Ingrid D'Silva (Wolters Kluwer Medknow Publications, 2003)
Epulis (localised gingival growth) is a common occurrence in the oral cavity. Since the complete gingival mucosa is a seat for trauma and/or irritation, no area in the oral cavity is immune to the occurence of epulides. This article presents a case of epulis in a 27 years old male, which appeared as a smooth gingival swelling clinically, but showed histopathological features of a well differentiated squamous cell carcinoma.